2006
DOI: 10.4049/jimmunol.177.4.2039
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 in T Cell-Mediated Liver Diseases: What’s Going On?

Abstract: The chemokine receptor CCR5 came into worldwide prominence a decade ago when it was identified as one of the major coreceptors for HIV infectivity. However, subsequent studies suggested an important modulatory role for CCR5 in the inflammatory response. Specifically, CCR5 has been reported to directly regulate T cell function in autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, and type 1 diabetes. Moreover, T cell-mediated immune responses are proposed to be critical in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 63 publications
(95 reference statements)
6
53
0
Order By: Relevance
“…The CCR5 affects the immune cell function,1 and thus, the CCR5-Δ32 mutation leads to decreased CCR5 expression and influences the function of these cells 3. In agreement with our results, Kalev and colleagues reported a lack of association between CCR5-Δ32 mutation and DN in native Estonian type 2 diabetic patients 2.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The CCR5 affects the immune cell function,1 and thus, the CCR5-Δ32 mutation leads to decreased CCR5 expression and influences the function of these cells 3. In agreement with our results, Kalev and colleagues reported a lack of association between CCR5-Δ32 mutation and DN in native Estonian type 2 diabetic patients 2.…”
supporting
confidence: 91%
“…Previous studies demonstrated that a mutation in the unique exon (exon 1) of the CCR5 and deletion of 32 nucleotides (also known as Δ32) leads to decreased expression and function of CCR5 2. Due to its immunomodulatory functions, the CCR5-Δ32 mutation seems to play a key role in autoimmune and inflammatory diseases 3. This study aimed to analyze the CCR5-Δ32 mutation in type 2 diabetic patients with and without diabetic nephropathy (DN).…”
mentioning
confidence: 99%
“…Moreover, in an in vivo migration experiment, we clearly demonstrated that CXCR3-deficient Tregs were less frequent in the liver of congenic mice upon Con A challenge compared with wt Tregs, verifying an impaired migration capacity of Tregs lacking CXCR3. It has to be remembered that non-lymphoid tissue-homing Tregs also express further chemokine receptors beside CXCR3 (e.g., CCR5 and CCR6), which might also account for Treg recruitment to the inflamed site (27)(28)(29)(30). Hence, we did not expect a complete lack of Tregs in the liver of CXCR3 2/2 mice, and, moreover, a total loss of Treg recruitment to target tissue might have resulted in an even more pronounced phenotype of naive CXCR3 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5, having CCL3 (macrophage inflammatory protein 1␣), CCL4 (macrophage inflammatory protein 1␤), and CCL5 (regulated upon activation, normal T cell expressed and secreted chemokine) as ligands, is also implicated in inflammatory diseases such as rheumatoid arthritis (Prahalad, 2006) and in autoimmune diseases such as multiple sclerosis and type 1 diabetes (Proudfoot, 2002;Ajuebor et al, 2006).…”
mentioning
confidence: 99%